Examining the contemporary ethno-national policy: a comprehensive analysis of the political rights and legal status of indigenous peoples - Vitaliy Kovalchuk; Yurii Kovnyi; Mykhailo Prokhorenko; Kateryna Manuilova; Svitlana Poliarush-Safronenko (Jurídicas, 2023)
The article delves into the contemporary legal and political status of indigenous communities within contemporary frameworks. It traces the evolutionary trajectory of pertinent regulations, analyzes contemporary legal terminologies, and sheds light on the political rights of indigenous populations. A primary focus is directed towards acknowledging and honoring their autonomy and self-determination within the legal framework of the state. Employing a comparative legal methodology, the analysis scrutinizes the regulatory landscape concerning the status of indigenous peoples across various countries, including the USA, Canada, New Zealand, Indonesia, Sweden, Norway, and Ukraine. To support the author’s assertions, a survey methodology was adopted to gather data from different regions of Ukraine and gauge perceptions of the status of indigenous peoples and their socio-political situation. The article concludes that despite discernible advancements, numerous indigenous communities worldwide continue to encounter challenges in exercising their political rights to their fullest extent.